ENGLISH LEARNING STYLES ON HIPPOCRATES GANUS’S PERSONALITY TYPES (AT SMAN 5 MAKASSAR) - Pondaag, Samuel Siloam; Farahdiba, Syarifah; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2025)
This study aimed to find out how Hippocrates Ganus’s personalities tendency towards English learning styles based on auditorial, visual, and kinesthetic. This study used a qualitative descriptive method and data was collected through observation, personality test and interview. The observation was performed, involve seven students. The aim of this study was to reveal the personalities of students with English learning styles at SMAN 5 Makassar. Through interviews conducted, it was found that seven students have different personalities, however some students have similar learning styles. Phlegmatic personality has a tendency to like quiet learning but student is not fond of learning approaches that emphasize a lot of physical movement. As well as students with choleric and melancholic personalities who prefer a quite learning environment over engaging in excessive physical activity. Similarly, pupils who possess choleric and melancholy dispositions often choose a tranquil learning environment rather than engaging in physical engagements from a distance. On other hand, student with a sanguine disposition tend to choose a kinesthetic learning method which is very stimulating due to its emphasis on physical activity rather than silent study.